Using multimedia in teaching Islamic studies - Wan Jusoh, Wan Noor Hazlina; Jusoff, Kamaruzaman (Academic Journals, 2009)
The sophistication of multimedia technologies nowadays gives a great challenge to educators in order to continuously play significant roles in the borderless globalisation of information era. This challenge should not be regarded as a threat but should be accepted as a great reward to education world, which is able to produce an amazing result if the tools are used correctly and wisely. Thus, the main purpose of this paper is to discuss the use of multimedia in teaching and learning process. In this paper, researcher will share their experience in teaching Islamic Studies in Taylor’s University College, Subang Jaya, Selangor, Malaysia using multimedia as beneficial tools in enhancing learning process. In Islamic education, human’s achievement in Information Communication Technology (ICT) is a sign of knowledge achievement that need to be used to find the truth. Hence, in order to guide students towards the truth and simultaneously to make the teaching and learning process enjoyable, researcher had used various multimedia tools. Among them are PowerPoint slides, video clips, mind map and internet. As a result, students found that Islamic Studies subject is very interesting and entertaining and it can be proven that it is not impossible to transform a dry and plain subject to be fun and interactive lesson.